Depression, anxiety and their associated factors among patients with tuberculosis attending in Gondar city health facilities, North West Ethiopia - Solomon Assefa; Berhanu Boru; Daniel Ayelegne Gebeyehu; Bewuketu Terefe (BMC Psychiatry, 2023)
Abstract Introduction Depression and anxiety are the most prevalent mental disorders in the general population and are expected to be the number one global burden of disease by the year 2030. They are also common comorbid conditions for patients with tuberculosis. Objective This study aimed to assess the prevalence of symptoms of depression, and anxiety and their associated factors among patients with tuberculosis attending Gondar city health facilities. Methods An institution-based cross-sectional study was conducted from September 01 to 30/2020. A census sampling technique was employed to select 390 patients. A structured interviewer-administered questionnaire was used to collect data, and a standardized hospital anxiety and depression scale was used to measure the symptoms of anxiety and depression. Data were entered in Epi-Info version 7 and analyzed using SPSS version 23. Binary and multivariable logistic regressions were computed to identify factors associated with the symptoms of depression and anxiety. P-value < 0.05 and adjusted odds ratios were used to declare the significance and strength of the association. Results The overall prevalence of symptoms of depression and anxiety were found to be 35.8% with 95% CI (34.6, 36.6). Perceived stigma and duration of illness > 12 months were associated positively ([AOR = 3.60; 95% CI (2.74, 4.43)], and [AOR = 3.19; 95% CI (2.17, 4.19)]) for both depression and anxiety respectively. Separate analyses revealed that the prevalence of symptoms of depression was 55.9% (95% CI (51.0%, 60.3%) and was significantly associated with duration of illness 4–6 months and > 12 months (AOR = 1.21; 95% CI (1.17, 2.73)] and [AOR = 2.36; 95% CI (2.16, 3.79)], comorbid chronic disease (AOR = 0.12; 95% CI (0.08, 0.91)] and perceived stigma [AOR = 0. The prevalence of anxiety symptoms was 39.5 percent, with 95% confidence intervals of 34.6% and 44.6%, and it was significantly associated with comorbid chronic disease [AOR = 2.53; 95% CI (1.96, 6.32)] and perceived stigma [AOR = 3.31; 95% CI (1.22, 7.74)]. Conclusion The prevalence of symptoms of depression and anxiety was high. Duration of illness, comorbid chronic disease, and perceived stigma were significantly associated with symptoms of depression. Comorbid chronic disease and perceived stigma were significantly associated with symptoms of anxiety.